Rapid changes in the global carbon cycle - Halloran, P; Paul Richard Halloran (2008)
﻿ The flux of carbon in to and out of the atmosphere exerts a fundamental control over the Earth's climate. The oceans contain almost two orders of magnitude more carbon than the atmosphere, and consequently, small fluctuations within the oceanic carbon reservoir can have very significant effects on air-sea CO2 exchange, and the climate of the planet. Pelagic carbonates represent a major long-term flux of carbon from the surface ocean to deep-sea sediments. Within sediments, the biologically produced carbonates act as a longterm carbon store, but also as chemical recorders of past surface ocean conditions. Counterintuitively, despite the production and sedimentation of carbonate acting as a CO2 sink, over periods shorter than the mixing-time of the ocean, the pH change associated with calcium carbonate precipitation enriches the surface waters in CO2 and elevates the equilibrium value of gaseous exchange with the atmosphere. Coccolithophores, ubiquitous marine photosynthetic plankton, produce calcium carbonate plates, coccoliths, which account for around one third of all marine calcium carbonate production. Sedimentary coccoliths therefore represent a valuable repository of surface ocean geochemical data, as well as a very significant carbon-cycle flux. This thesis examines how the mass of calcium carbonate produced by coccolithophores has changed in response to rising levels of atmospheric CO2. A -40% increase in average coccolith mass over the last 230 years, paralleling anthropogenic CO2 release, is demonstrated within a high-accumulation rate North Atlantic sediment core. Additionally, a flow-cytometry method is presented, which enables the automatic separation of coccoliths from clay particles in sedimentary samples, representing the first step in a coccolith cleaning procedure, which should ultimately enable down-core measurements of coccolith trace-element/calcium ratios. Complementing this work I describe results from continuous dissolution analysis of cultured coccoliths which allows a first-order evaluation of trace-element partitioning into coccoliths produced by the species Coccoliths pelagicus, and present a conceptual methodology to allow the determination of single-species coccolith chemical data.